Hepatoblastoma in a 14-months old child - Shrestha, Rashes; Bhattarai, Niraj; Thakur, Binay; Devkota, Mukti; Mandel, Rajesh Kumar; Adhikari, Purushottam (Nepalese Journal of Cancer, 2021)
In children, commonest liver tumor is hepatoblastoma. We present a 14-month-old male child who presented with abdominal distension and loose stool. Radiological imaging revealed solid hepatic mass. Hematological investigations revealed anemia, thrombocytosis and high Serum alpha fetoprotein (AFP) level. Ultrasound (USG) guided FNAC confirmed the mass to be hepatoblastoma. CT scan revealed hepatoblastoma PRETEXT stage III. The patient underwent 6 cycles of neoadjuvant chemotherapy and responded to POSTTEXT stage II. Left hemi-hepatectomy was done with clear resectin margins. Complete surgical excision of the mass after preoperative chemotherapy remains the mainstay of the treatment of locally advanced hepatoblastoma.